2018
DOI: 10.1364/ol.43.001479
|View full text |Cite
|
Sign up to set email alerts
|

Flying particle microlaser and temperature sensor in hollow-core photonic crystal fiber

Abstract: Whispering-gallery mode (WGM) resonators combine small optical mode volumes with narrow resonance linewidths, making them exciting platforms for a variety of applications. Here we report a flying WGM microlaser, realized by optically trapping a dye-doped microparticle within a liquid-filled hollow-core photonic crystal fiber (HC-PCF) using a CW laser and then pumping it with a pulsed excitation laser whose wavelength matches the absorption band of the dye. The laser emits into core-guided modes that can be det… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 31 publications
0
16
1
1
Order By: Relevance
“…Remote sensing of electric field, temperature and irradiation was demonstrated using charged particles and fluorescent particles respectively with a spatial resolution down to tens [136], © 2018 Springer Nature; e, Ref. [137], © 2016 OSA of microns [128,131,132]. In this scheme, the trapped particle responds locally to the sensing quantities when it is passing through the region of interest and, determined by the particle's properties, it can react in different degrees of freedom including transverse motion, variations in speed, fluorescence radiation, etc.…”
Section: Hc-pcf Fotsmentioning
confidence: 99%
See 1 more Smart Citation
“…Remote sensing of electric field, temperature and irradiation was demonstrated using charged particles and fluorescent particles respectively with a spatial resolution down to tens [136], © 2018 Springer Nature; e, Ref. [137], © 2016 OSA of microns [128,131,132]. In this scheme, the trapped particle responds locally to the sensing quantities when it is passing through the region of interest and, determined by the particle's properties, it can react in different degrees of freedom including transverse motion, variations in speed, fluorescence radiation, etc.…”
Section: Hc-pcf Fotsmentioning
confidence: 99%
“…In addition to plasmonic FOTs, whispering-gallery mode (WGM) resonators based on HC-PCF traps combine small optical mode volumes with narrow resonance linewidths, making them great candidates for single photon sources. Zeltner et al constructed a WGM microlaser consisting of a dye-doped particle optically trapped in the core of HC-PCF [132]. SPS is theoretically possible if the resonator can achieve a higher Q factor.…”
Section: Single-photon Sourcesmentioning
confidence: 99%
“…Since Garrett et al demonstrated the first WGM lasers in 1961 2 , WGM microresonators have been widely used in the field of microlasers because of the high Q factor and the small mode volumes 8,25,53,[61][62][63][64] . Due to these advantages, microlasers based on WGM microresonators can obtain an ultralow lasing threshold.…”
Section: Microlasersmentioning
confidence: 99%
“…For example, nanothermometers in a form of fluorescent nanoparticles doped with Er 3+ dopants have been used to measure the temperature of living cells [25]. Local temperature sensing can also be performed by using rare-earth doped tips of optical fibres [26] or using WGM spectrum of a single dye-doped particle inside a hollow fibre [27]. Substances inside the measured sample can significantly distort the signal by absorption and presence of addition signals, such as autofluorescence and Raman peaks.…”
Section: Introductionmentioning
confidence: 99%